The Influence Of Leadership, Training, Inter-Human Relationship, Work Ethics And Teamwork On Work Productivity Of Employee Office Of The Ministry Of Religion, Muara Enim District - Yanimansyah Yanimansyah; Abdul Hamid; Yusnawati Yusnawati (Penerbit Jurnal Indonesia, 2023)
The aim of the study was to determine and analyze the influence of leadership, training, human relations, work ethics and teamwork individually and collectively on the work productivity of the employees of the Office of the Ministry of Religion, Muara Enim Regency. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. The results of the research show that leadership has a significant effect on the work productivity of the employees of the Office of the Ministry of Religion, Muara Enim Regency. Training has a significant effect on work productivity. Human relations have a significant effect on work productivity. Work ethic has a significant effect on work productivity. Team work has a significant effect on work productivity. Leadership, training, human relations, work ethics and teamwork have a significant effect on the work productivity of the employees of the Office of the Ministry of Religion, Muara Enim Regency.